The Relationship Between Digital Data Security Awareness Perception, Financial Literacy and Digitalization (Third Sector Social Economic Review, 2026)
The examination of the relationship between digital data security awareness perception, financial literacy, and digitalization is of great importance in understanding how individuals perceive the risks they encounter in the digital financial environment and how they manage these risks. In this context, the study aims to examine the relationship between the digital data security awareness perceptions and the levels of financial literacy and digitalization of associate and undergraduate students studying at Siirt Üniversitesi. The data were collected between 17.03.2025 and 12.05.2025 using the observation method and a survey form, and the data obtained from 507 respondents were included in the analysis. In the analysis of the data, descriptive statistics, correlation, regression, t-test, and ANOVA analyses were utilized. In the analysis findings, it was observed that as students’ digital data security awareness perception increased, their levels of financial literacy and digitalization also increased; that the levels of financial literacy and digitalization differed according to whether students used a credit card/additional card; and that there was a difference in terms of financial literacy and digitalization levels between students who had taken a finance course and those who had not. The findings have once again highlighted the importance of education in finance and digitalization. It is anticipated that addressing the relationship between digital data security awareness perception and financial literacy and digitalization together will make significant contributions to the literature.
Keywords: Digital Data; Digital Data Securit; Financial Literacy; Digitalization; Financial Technology